A Prospective, Holistic, Multicenter Approach to Tracking and Understanding Bloodstream Infections in Pediatric Hematology-Oncology Patients. (12th April 2017) - Gaur, Aditya H.; Bundy, David G.; Werner, Eric J.; Hord, Jeffrey D.; Miller, Marlene R.; Tang, Li; Lawlor, John P.; Billett, Amy L.
Abstract : OBJECTIVE: To assess the burden of bloodstream infections (BSIs) among pediatric hematology-oncology (PHO) inpatients, to propose a comprehensive, all-BSI tracking approach, and to discuss how such an approach helps better inform within-center and across-center differences in CLABSI rate DESIGN: Prospective cohort study SETTING: US multicenter, quality-improvement, BSI prevention network PARTICIPANTS: PHO centers across the United States who agreed to follow a standardized central-line–maintenance care bundle and track all BSI events and central-line days every month. METHODS: Infections were categorized as CLABSI (stratified by mucosal barrier injury–related, laboratory-confirmed BSI [MBI-LCBI] versus non–MBI-LCBI) and secondary BSI, using National Healthcare Safety Network (NHSN) definitions. Single positive blood cultures (SPBCs) with NHSN defined common commensals were also tracked. RESULTS: Between 2013 and 2015, 34 PHO centers reported 1, 110 BSIs. Among them, 708 (63.8%) were CLABSIs, 170 (15.3%) were secondary BSIs, and 232 (20.9%) were SPBCs. Most SPBCs (75%) occurred in patients with profound neutropenia; 22% of SPBCs were viridans group streptococci. Among the CLABSIs, 51% were MBI-LCBI. Excluding SPBCs, CLABSI rates were higher (88% vs 77%) and secondary BSI rates were lower (12% vs 23%) after the NHSN updated the definition of secondary BSI ( P <.001). Preliminary analyses showed across-center differences in CLABSI versus secondary BSI and between SPBC and CLABSI versus non-CLABSI rates. CONCLUSIONS: Tracking all BSIs, not just CLABSIs in PHO patients, is a patient-centered, clinically relevant approach that could help better assess across-center and within-center differences in infection rates, including CLABSI. This approach enables informed decision making by healthcare providers, payors, and the public. Infect Control Hosp Epidemiol 2017;38:690–696